RELIGION AND CASTE AS POLITICS IN JAVANESE CULTURAL DIVERSITY - Ilham Solihin; Nada Nabilah Syafiqoh; Muthia Nur Fadhilah (The Pontianak State Institute of Islamic Studies, 2023)
In this article, Religion and Caste as Politics in Javanese Cultural Diversity, the author focuses on religion and caste as a form of politics that runs in Javanese culture. Javanese culture and Islam are two patterns and points that are difficult to separate. Because both of them will have a broad impact in creating various outcomes of extraordinary existence and will even give a very unique impression on its subtle and shady features so that what happens in the discussion of Javanese culture can hardly be separated from Islam, even this is also true. will be the basis of which is included in the political field. The ideas brought about by the concepts brought by Islam and Java continue to emerge and even continue to be something better and more advanced, especially those contained in various different but similar perspectives. Then since Geertz began to conduct various studies on The Religion of Java, various kinds of studies continued, while various opinions emerged, those who agreed with it or those who rejected it. This paper takes the points and patterns that are in the study carried out by a Geertz while the discussion revolves around the concept presented by him about his trichotomy. However, from various opinions that provide an overview of the strengths or weaknesses of Geertz's conception, Geertz's conception still exists as an option in providing an explanation that tells about how Javanese religion, even from this concept, has become a source of inspiration and continues in the study of Javanese culture. This research generates questions in the form of how the political concept of Javanese people in religion and caste. The approach used in this research is the knowledge of sociology, Emile Durkheim. Thus the article summarizes the findings obtained, namely caste as a political social status, Javanese culture as a political mechanism for Javanese people.